Analysis of Numerical Ability Students on Chemical Equilibrium - Mustapa, Kasmudin; Rahmawati, Nur; Ratman, Ratman; Marpaung, Meida Esterlina; Mawaddah, Hayyatun (Journal of Disruptive Learning Innovation (JODLI), 2023)
This study aims to determine the level of numerical ability in class XI students of SMA Negeri 1 Parigi Kab. Parigi Moutong. This research was carried out from January to March 2023. The research method used is quantitative descriptive. Data analysis using descriptive statistics. The sampling technique is random sampling. The research instrument used was a description numerical ability test. The results showed that the level of students' numerical abilities on the indicators of performing mathematical calculations was in the low category, with a percentage of 28.44%. The logical thinking indicator obtained low category results with a percentage of 28.24%. The problem-solving indicator obtained a very low category result of 11.45%. On indicators recognising patterns and relationships between numbers, results with a percentage are in the very low category. Data on the results of students' numerical abilities at SMA Negeri 1 Parigi are categorised as very low. The results of this study are expected to be a source of information regarding the numerical ability of class XI students in chemical equilibrium material.